Xenobiotic Effects of Chlorine Dioxide to Escherichia coli O157:H7 on Non-host Tomato Environment Revealed by Transcriptional Network Modeling: Implications to Adaptation and Selection - Shu, Xiaomei; Singh, Manavi; Karampudi, Naga Bhushana Rao; Bridges, David F.; Kitazumi, Ai; Wu, Vivian C. H.; De los Reyes, Benildo G. (Frontiers in Microbiology, 2020)
Escherichia coli serotype O157:H7 is one of the major causing agents of outbreaks associated with fresh fruits and vegetables. Gaseous chlorine dioxide (ClO2) has been reported to be an effective intervention to eliminate bacteria on fresh produce. Although a remarkable scenario was reported in E. coli exposed to low dose of ClO2, regulatory mechanisms coordinating ClO2 exposure and potential bacterial adaptation remind unclear. This study examined the temporal transcriptome of E. coli O157:H7 during exposure to different doses of ClO2 in order to elucidate the genetic mechanisms of how E. coli survive under these harsh environmental conditions. Three doses of 1, 5 and 10 µg ClO2 per gram of tomato fruits cause different effects depending on dose and exposure time. First hour of 1 and 5 µg ClO2 exposure caused only partial killing, with significant growth reduction starting at the second hour, while without further significant growth reduction at third hour. However, 10 µg ClO2 exposure led to massive bacterial cell death at 1 hour, with further increased cell death at 2 and 3 hours. First hour of 1 µg ClO2 exposure caused activation of primary defense and survival mechanisms; but defense response was attenuated during the second and third hours. Upon 5 µg ClO2 treatment, transcriptional networks showed massive downregulation of pathogenesis and stress response genes at the first hour of exposure, with the number of differentially expressed genes to be decreased at the second and third hours. In contrast, more genes were downregulated when the bacteria were exposed to 10 µg ClO2 at the first hour, with the number of both up and downregulated genes to be decreased at the second hour. However, a total of 810 genes were uniquely upregulated at the third hour when the bacteria were treated with 10 µg ClO2, suggesting that the potency of xenobiotic effects had led to potential adaptation. This study provided important knowledge in selection of target molecules for eliminating the bacterial contamination in fresh produce without overlooking potential risks of adaptation.